Correlation Between Classical Fisher Information and Quantum Squeezing Properties of Gaussian Pure States (Journal of Atomic and Molecular Sciences, 2010)
The Fisher information of Gaussian pure states is studied in this work. Based on the definition of joint non-classical properties, we calculate the non-classical properties of Gaussian pure states. The results show that the Fisher information and Fisher length are efficacious tools to study the non-classical properties of quantum states. And the non-classical properties of states can be used to calculate the quantum properties quantificationally. Making use of Fisher information, one can obtain the correlation between the Fisher information and quantum squeezing properties of Gaussian pure states. Especially, it is significative that one can quantificationally describe the fluctuation of quantum states by an alternative new method.
Keywords: Gaussian pure states; Fisher information; Fisher length; joint non-classical properties.